Design of multiband microstrip patch antenna with bandwidth enhancement for wireless communication system - Ahmed Abdulkareem Ahmed; Fares Saleh Alatallah; Y. E. Mohammed Ali2 (Tikrit Journal of Pure Science)
This research work presents analysis of multiband rectangular microstrip  patch antenna for globalsystem for mobile communications at 0.9455GHz and 1.7595GHz and wireless local area Network at 2.4635 GHZ and 5.15 GHz and WiMAX at 3.5745GHz and international  mobile telecommunications (IMT) at 4.46 GHz . An antenna is  designed using FR4-(epoxy) substrate material with thickness1.6 mm and dielectric constant of 4.3. The microstrip antenna has a patch dimension of 83.33mm×45mm. The antenna has minimum return loss of - 32.563 dB at 0.9455GHz, -27.226 dB at 1.7595 GHz, -29.136 dB at 2.4635GHz, -31.621 dB at 3.5745GHz, -36.531dB at 4.46 GHz, -25.613 at 5.15 GHz. In this antenna designed the maximum gain of  2.20 dB at 0.9455GHz, 3.17 dB at 1.7595 GHz, 5.68 dB at 2.4635GHz , 7.04 dB at 3.5745 GHz, 6.08 dB at 4.46GHz, 5.26 dB at 5.15 GHz. The simulation of the design antenna is done using the software computer simulation technology CST